Quasi-Crystal Metasurface for Simultaneous Half- and Quarter-Wave Plate Operation. Issue 1 (December 2018) - Mustafa, Meraj-E-; Amin, Muhammad; Siddiqui, Omar; Tahir, Farooq
Abstract We present a quasi-crystal metasurface that can simultaneously work as efficient cross-polarizer and circular polarizer for wide range of frequencies. The quasi-crystal technique benefits from individual resonant response of anisotropic patch and the coupled response due to periodic perturbations in the square lattice. It is shown that quasi-crystals offer broadband response for cross-polarization as well as high efficiency circular-polarization conversion of reflected fields. The quasi-crystal metasurface achieves cross-polarization (above −3 dB) for two broad frequency bands between 10.28–15.50 GHz and 16.21–18.80 GHz. Furthermore, the proposed metasurface can simultaneously work as high efficiency circular-polarizer from 10.15–10.27 GHz and 15.51–16.20 GHz. The metasurface design is also optimized to suppress co-polarization below −10 dB between 10.5–15.5 GHz. This metasurface can find potential applications in reflector antennas, imaging microscopy, remote sensing, and control of radar cross-section etc.